Activatable cancer sono-immunotherapy using semiconducting polymer nanobodies - Zeng, Ziling (2022)
Despite the great promises of sonodynamic therapy (SDT) in combination cancer therapy, its clinical applications are hindered by the "always-on" pharmacological activities of therapeutic agents and the lack of efficient sonosensitizers. Herein, the development of semiconducting polymers as efficient sonosensitizers and further development of sono-immunotherapeutic nanobodies (SPNAb ) for activatable cancer sono-immunotherapy are reported. Conjugation of anti-CTLA-4 antibodies onto the polymer nanoparticles through a 1 O2 -cleavable linker affords SPNAb with relatively low CTLA-4 binding affinity. Upon sono-irradiation, SPNAb generates 1 O2 not only to elicit a sonodynamic effect to induce immunogenic cell death, but also to release anti-CTLA-4 antibodies and trigger in situ checkpoint blockade. Such a synergistic therapeutic action mediated by SPNAb modulates the tumoricidal function of T-cell immunity by promoting the proliferation of cytotoxic T lymphocytes and depleting immunosuppressive regulatory T cells, resulting in effective tumor regression, metastasis inhibition, durable immunological memory, and prevention of relapse. Therefore, this study represents a proof-of-concept sonodynamic strategy using semiconducting polymers for precise spatiotemporal control over immunotherapy.